Tid til kvalitetsmåling?: Studier af indrulleringsprocesser i forbindelse med introduktionen af kliniske kvalitetsdatabaser i speciallægepraksissektoren - Marius Brostrøm Kousgaard (Copenhagen Business School (CBS), 2008)
– Since the late 1980s, concerns over quality of care have become a significant challenge to health care sectors across Europe, and numerous initiatives of quality assessment and improvement have been launched. In several western countries the idea of measuring the quality of clinical care by means of "quality indicators” has increasingly captured the attention of policy makers. In Denmark this development has been relatively pronounced, and today the principles of indicator monitoring constitute a crucial component in the national strategy of quality development. The so-called "clinical databases” are the oldest of the current indicator arrangements and this dissertation deals with the introduction of clinical databases in a particular branch of the health care sector where practising specialists in privately owned clinics offer medical services in accordance with collectively agreed reimbursement schemes. Inspired by actor-network theory this dissertation investigates the relations between the databases, their spokespersons, and the practising specialists who are supposed to be enrolled in the databases. The objective is to identify and articulate the various problematizations, interests, concerns, challenges and transformations that are involved in the process of enrolment.
hdl:10398/6862
Keywords: 650